Features of calculation and payment of vat on customs operations in the eurasian economic community (Journal of Economic Research & Business Administration, 2016)
Application of international practice in the regulation of foreign trade of Kazakhstan, in the future, contribute actively and effectively conduct trade policy. Entering a foreign market gives opportunity to learn about international and national contingent positions of exportimport commodity flow. This article describes some of the features of the order, calculation and payment of VAT on customs operations between member countries of the Customs Union in accordance with regulatory legislative acts.
Keywords: Eurasian Economic Community; Customs Union; export and import of goods; indirect taxes.